Case report: A nodular lesion in the ventral region of the neck in the rat as a starting point for considerations on differential diagnosis - Godlewska, Agata; Dolka, Izabella; Borowczak, Ilona; Chomutowska, Ewa; Przeworski, Mirosław; Różycka, Katarzyna; Barszcz, Karolina (Frontiers in Veterinary Science, 2024)
The purpose of this case report is to present a poorly differentiated sarcoma in a pet rat. A veterinarian detected a small-sized nodular lesion in the ventral region of the neck during a follow-up visit related to another ailment. The anatomical structures found in the neck region in the rat and the differential diagnosis when deformities are palpated in this body part are discussed in detail. The patient underwent a total of four surgical procedures, as well as radiotherapy and chemotherapy. The rat survived in good condition for 144 days after finding the tumor.